Teaching Grammar in Intermediate English Grammar Class: What is Happening beyond the Classroom? - Oktavinanda, Giovanni; Fikroni, Moh. Rofid; Umroh, Juzma Fiatul (Journal of Language Intelligence and Culture, 2023)
Teaching grammar is a very complex task to do since the lecturer does not only teach the rules but also teach other aspects of language. As language component, grammar will always play a significant role within the English skills such as listening, speaking, reading, and writing. In relation to this regard, this study exposed the practice of teaching grammar at intermediate grammar class as a part of grammar courses in State University of Malang and seek for the issues of what was happening beyond the classroom which encompassed lecturer’ role, students’ role, classroom management strategy, approach, technique, materials, tasks, language used, lecturer-students interaction, and students’ participation in teaching and learning process. This study used both qualitative and quantitative research approach where the results were described quantitatively in numbers and qualitatively in words describing the phenomena taking place. The results suggested that the teaching and learning process of intermediate grammar at State University of Malang manages to meet almost all of the indicators and criteria within the aspects measured in the observation checklist. The teaching and learning process manages to meet 86.2 % of the indicators which means it meets 50 indicators out of 58. Thus, the teaching ang learning process can be considered as excellent.